Synergistic Effects of Gypsum and Cement on the Geotechnical Properties of Clay Soils: Experimental Evaluation of CBR, UCS, and Compaction Characteristics - Basral Anugrah; Haiban Haiban (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
Expansive clay soils are widely recognized as problematic subgrade materials due to their high plasticity, low strength, and pronounced swelling–shrinkage behavior. This study investigates the synergistic effect of gypsum and cement as stabilizing agents for clay soils. Laboratory tests were conducted on 96 soil specimens, with stabilizer contents of 1%, 3%, and 5% (by dry weight) and curing periods of 1, 7, and 14 days. Standard tests, including Atterberg limits, compaction, California Bearing Ratio (CBR), and Unconfined Compressive Strength (UCS), were performed according to ASTM/SNI standards. Results demonstrate that the combined use of gypsum and cement significantly reduces the plasticity index from 41.54% to 8.35% and increases CBR from 1.99% to 23.65% after 14 days of curing. UCS values also improved, reaching a peak of 1.84 MPa under optimum stabilization conditions (5% additive, 14 days curing). These improvements are attributed to cation exchange and pozzolanic reactions that form calcium silicate hydrate (C–S–H) and calcium aluminate hydrate (C–A–H) phases, enhancing soil particle bonding and reducing voids. The findings indicate that combined gypsum–cement stabilization is not only effective in improving mechanical properties but also modifies the soil classification from high plasticity clay (CH) to low plasticity clay (OL). This research contributes practical guidelines for road subgrade improvement and advances the scientific understanding of chemical–mineral interactions in soil stabilization.